Modeling and visualization of functional 3D objects in the professional training of future vocational education teachers - Derevyanchuk, Oleksandr; Ushenko, Yurii; Lovska, Alyona; Ravlyuk, Vasyl; Balovsyak, Serhiy (Edelweiss Applied Science and Technology, 2026)
The article presents a methodology for implementing comprehensive STEM projects in the training process of higher education learners in engineering-pedagogical specialties of a general technical or technological (in the field of mechanical engineering) profile. As an example, the study proposes teaching students how to build and analyze models of functional 3D objects, as well as how to visualize them as part of comprehensive STEM projects. The active integration of 3D modeling and 3D visualization into the educational process aims at integrating scientific knowledge in technology, engineering, and mathematics through solving practical tasks and analyzing real challenges of professional activity. Modeling and visualization of 3D objects, in particular, make it possible to gain deeper insight into the study of the features of functional 3D objects and contribute not only to mastering abstract mathematical concepts but also to the development of logical and spatial thinking. As an example of a possible way to implement comprehensive STEM projects in the educational process, the stages of the project “Modeling and Visualization of Functional 3D Objects” are highlighted. The project includes the analysis, modeling, and visualization of functional 3D objects in the SolidWorks Simulation software suite and the printing of a physical model on a 3D printer.